2021
DOI: 10.1159/000519385
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019: COSeSco – A Risk Assessment Score to Predict the Risk of Pulmonary Sequelae in COVID-19 Patients

Abstract: <b><i>Background:</i></b> The presence of interstitial pneumonia in coronavirus disease 2019 (COVID-19) patients, as diagnosed through laboratory, functional, and radiological data, provides potential predicting factors of pulmonary sequelae. <b><i>Objectives:</i></b> The objectives were the creation of a risk assessment score for pulmonary sequelae at high-resolution computed tomography (HRCT) through the assessment of laboratory data, lung function, and radiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…These data are even more worrisome than ours, probably because this group focused on invasively ventilated patients. Further studies are needed to create or validate scores to identify patients at high risk of pulmonary sequelae on chest CT ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data are even more worrisome than ours, probably because this group focused on invasively ventilated patients. Further studies are needed to create or validate scores to identify patients at high risk of pulmonary sequelae on chest CT ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…These prospective cohorts of patients already point to a high prevalence of pulmonary involvement represented by an abnormal DLCO and many chest CT findings. This is especially important in those with the most severe disease in the acute phase, where 54% of patients (22). Although all of these studies assessed pulmonary sequelae after COVID-19 at 12 months (8,10,20), none of them provided information about the clinical management and follow-up in a real post-COVID consultation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that in COVID-19 survivors, the main pulmonary function abnormalities were a reduction in DLco with an almost normal DLco/VA and a reduction in FVC and TLC with an increase in the FEV 1 /FVC ratio [ 2 , 3 , 7 , 8 , 10 , 11 , 12 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Respiration, Aiello et al [ 13 ] reported the results of a prospective, observational, single-center study of a large cohort of subjects who suffered from COVID-19 pneumonia during their follow-up post-hospital admission. They collected changes in clinical and functional data to identify risk factors for high-resolution computer tomography (HRCT) sequelae in COVID-19 patients after hospitalization and to test the usefulness and clinical relevance of the COSeSco score (COVID-19 Sequelae Score), which includes age, body mass index, comorbidities, and D-dimer at the time of hospitalization, as well as exercise capacity and dyspnea at follow-up, for the prediction of developing pulmonary sequelae at HRCT.…”
mentioning
confidence: 99%